A Systematic Review of Randomized Controlled Trials on Interventions Adopting Body-Mind-Spirit (BMS) Model on Holistic Well-Being - Tongtong Li MHA, MS; Xinyue Hu MS; Iris Chi DSW (SAGE Publishing, 2022)
Background This systematic review aims to examine existing randomized controlled trials on interventions adopting Body-Mind-Spirit (BMS) model and evaluated the effectiveness of holistic well-being outcomes. Following three key concepts of the BMS model, our review questions included (1) How was BMS defined? (2) What activities were included, and how were they related to BMS dimensions? (3) What were interventionists' backgrounds, and whether they received BMS training? (4) What were holistic outcomes? and (5) What were the effectiveness and qualities of studies? Methods Searches were performed using nine databases for the studies published through August 2020. The process follows PRISMA protocol, and the "risk of bias" tool from the Cochrane Handbook was utilized to determine the quality of included studies. Results Across 20 included studies, 18 (90%) presented a BMS definition, but only seven (35%) included all three key concepts of the BMS model. Eight studies (40%) offered detailed descriptions of body, mind, and spirit sections, and 12 (60%) mentioned cultural factors. Only five (25%) specified the body, mind, and spirit activities, and only three (15%) reported the BMS training in detail. Seven studies (35%) showed effectiveness in holistic outcomes. Only three (15%) were considered as high quality. Conclusion A unified definition of the BMS model and the guideline to apply the BMS model to design and implement interventions are highly recommended to provide a standard framework for researchers to conduct future studies. The reason for low quality is because the lack of adequate allocation concealment and blindings.